(Section) (Section) (Section) (Section) (Section) (Section)
(Section) (Section) (Section) (Section) (Section) (Section)
(Section) (Section) (Section) (Section) (Section) (Section)
1
A STUDY ON LAPLACE SUBSTITUTION
REXLINMARY.A
Department of Mathematics
1 INTRODUCTION 1
2 PRELIMINARIES 6
2.1 Definitions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 6
4 Main Results 16
5 References 26
i
Chapter 1
INTRODUCTION
Many Differential equation arising from physical problems are linear but have vari-
able coefficients and do not permit a general analytical solution interms of known
tial equations dates back to the mid seventeenth century when both I saac Newton
(1642 − 1727) and Gottfried Wilhelm Leibnitz (1646 − 1716) had been busy discover-
ing the fundamentals of calculus. Leibnitz was developed the notation and the integral
equations to separable ones and the procedure for solving first order linear equations.
After the Bernoulli brothers brought forth the solution of many typical differential
equations.
1
The Bernoulli brothers Jakob (1654 − 1705) and Johan (1667 − 1748) , who
developed methods of solving differential equations, extended the range of their ap-
dy
plications to mechanics. In particular, Jakob solved the differential equation dx
=
h i 12
a3 dy y
(b2 y−a3 )
and in 1694 Johan was able to solve the equation dx = ax .
Leonard Euler (1707 − 1783) identified the condition for exactness of first order
differential equations; developed the theory of integrating factors and the general solu-
Joseph Lagrange (1736 − 1813) , who succeeded showed that the general solu-
variation of parameters. Pierre Simon de Laplace (1749 − 1827) famous for his monu-
∂2u 2 2
mental work on celestial mechanics studied extensively the equation ∂x2
+ ∂∂yu2 + ∂∂zu2 = 0,
by the nineteenth century almost all of the standard methods of solving ordinary and
partial differential equations were known. Many made significant contributions in this
direction and among them Picard, Runge, Kutta, Hilbert and Frobenius deserve special
mention.
of time into a function of complex frequency. The inverse Laplace transform takes a
2
complex frequency domain function and yields a function defined in the time domain.
The Laplace transform is related to the Fourier transform, but whereas the Fourier
the process of analyzing the behavior of the system, or in synthesizing a new system
based on a set of specifications. So, for example, Laplace transformation from the
time domain to the frequency domain transforms differential equations into algebraic
Simon Laplace, who used a similar transform (now called z transform) in his work on
probability theory. The current widespread use of the transform came about soon after
World War II although it had been used in the 19th century by Abel, Lerch, Heaviside,
and Bromwich. From 1744 , Leonhard Euler investigated integrals of the form
Z
z= X(x)eax dx
and
Z
z= X(x)xA dx
as solutions of differential equations but did not pursue the matter very far. Joseph
Louis Lagrange was an admirer of Euler and, in his work on integrating probability
3
density functions, investigated expressions of the form
Z
X(x)e−ax ax dx,
which some modern historians have interpreted within modern Laplace transform
theory.
1782 where he was following in the spirit of Euler in using the integrals themselves as
solutions of equations. However, in 1785 , Laplace took the critical step forward when,
rather than just looking for a solution in the form of an integral, he started to apply
the transforms in the sense that was later to become popular. He used an integral of
the form:
Z
xs φ(x)dx,
to look for solutions of the transformed equation. He then went on to apply the Laplace
transform in the same way and started to derive some of its properties, beginning to
appreciate its potential power. Laplace also recognised that Joseph Fourier’s method
of Fourier series for solving the diffusion equation could only apply to a limited region
of space as the solutions were periodic. In 1809 , Laplace applied his transform to find
4
Mixed partial derivatives: For a function of more than two variables, we can define
the second-order mixed partial derivative with respect to two of the variables (in a
particular order) in the same manner as for a function of two variables, where we treat
5
Chapter 2
PRELIMINARIES
2.1 Definitions
dy 2
+ dy9
Definition 2.1.2. The order of the highest derivative is called order y = x dx ( )
dx
order = 1
Definition 2.1.3. The power of the highest order derivative in the equation is called
n o3
dy 2
3 2
d y
the degree 1 + dx = a2 dx3 .
Order= 3
Degree= 2
6
Definition 2.1.4. A relation between the dependent variable and independent vareiable
Definition 2.1.5. The Laplace transform L , of a function f (t) for t > 0 is defined
R∞
Lf (t) = 0
e(−st)f (t)dt
and write:
Lf (t) = F (s)
Lg(t) = G(s)
Definition 2.1.6. If G(s) = Lg(t) , then the inverse transform of G(s) is defined as:
7
Property 2 : Shifting Property
Property 3 :
Rt
If L−1 G(L−1 s) = g(t) , then L−1 sG(s) = 0
g(t)dt .
Property 4 :
Definition 2.1.7. A differential equation is called as a linear equation if all the terms
of dependent variables and its derivatives are of first degree only, otherwise it is called
non-linear differential equation. The general Linear differential equation of n(th) order
dn y (n−1)
dxn
+ A1 ddxn−1y + ....An y = f (x)
8
s.no Laplace transform Inverse Laplace Transform
1
1 1 s
s>0
n!
2 xn sn+1
n = 0, 1...
1
3 eax s−a
s>a
a
4 sinax s2 +a2
s>0
s
5 cosax s2 +a2
s>0
a
6 sinhax s2 −a2
s > |a|
s
7 coshax s2 −a2
s > |a|
n!
8 xn eax (s−a)n+1
b
9 eax sinbx (s−a)2 +b2
s−a
10 eax cosbx (s−a)2 +b2
b
11 eax sinhbx (s−a)2 −b2
s−a
12 eax coshbx (s−a)2 −b2
xn−1 1
13 (n−1)! sn
n = 1, 2...
eax xn−1 1
14 (n−1)! (s−a)n
s>a
eax −ebx 1
15 a−b (s−a)(s−b)
a 6= b
aeax −bebx s
16 a−b (s−a)(s−b)
a 6= b
1 1
17 2a3
(sinax − axcosax) (s2 +a2 )2
s2 −a2
18 xcosax (s2 +a2 )2
Γk
19 xk−1 sk
k>0
20 √1 1
1
Πx s2
9
Chapter 3
LAPLACE SUBSTITUTION
METHOD
The aim of this section is to discuss the use of Laplace substitution method. We
consider the general form of non-homogeneous partial differential equation with initial
∂2u
Here L = ∂x∂y
, Ru(x, y) is the remaining linear terms in which contains only first
order partial derivatives of u(x, y) with respect to either x or y and h(x, y) is the
10
∂2u
∂x∂y
+ Ru(x; y) = h(x; y)
∂ ∂u
∂x ∂y
+ Ru(x; y) = h(x; y) → (3)
∂u
putting ∂y
= U in equation (3) ,we get
∂U
∂x
+ Ru(x; y) = h(x; y) → (4)
Taking inverse Laplace transform of equation (5) with respect to x ,we get
∂u(x;y)
∂y
= g(y) + L−1 1
x [ s Lx [h(x; y) − Ru(x; y)]] → (7)
This is the first order partial differential equation in the variables x and y . Taking
Taking the inverse Laplace transform of equation (8) with respect to y ,we get
11
u(x; y) = f (x) + L−1 1 −1 1
y [ s Ly [g(y) + Lx [ s Lx [h(x; y) − Ru(x; y)]]]] → (9)
The last equation (9) gives the exact solution of initial value problem.
∂2u
Example 3.1.1. Consider the partial differential equation ∂x∂y
= e−y cosx with initial
Solution:
∂2u
In the above initial value problem Lu(x; y) = ∂x∂y
, h(x; y) = e−y cosx and the
∂2u
∂x∂y
= e−y cosx → (1)
∂u
putting ∂y
= U in equation (2) ,we get
∂U
∂x
= e−y cosx → (3)
This is the non-homogeneous partial differential equation of the first order. Taking
12
∂u(x;y)
∂y
= e−y sinx → (5)
This is the partial differential equation of the first order in the variables x and y .
1
su(x; s) − u(x; 0) = sinx (1+S)
1
u(x; s) = sinx s(1+S) → (6)
This is the required exact solution of equation (1) . Which can be verify through
variables.
∂2u
Example 3.1.2. Consider the partial differential equation ∂x∂y
= sinxsiny with
∂2u
∂x∂y
= sinxsiny → (1)
Solution:
In the above example assume that ux (x; y) and uy (x; y) both are differentiable in
∂2u ∂2u
the domain of function u(x, y) . This implies that ∂x∂y
= ∂y∂x
. Given initial conditions
∂u
force to write the equation (1) in following form and use the substitution ∂y
=U.
∂ ∂u
∂x ∂y
= sinxsiny → (2)
∂U
∂x
= sinxsiny → (3)
13
Taking the Laplace transform of equation (3) with respect to x , we get
−2siny
U (s; y) = s
+ siny[ 1s − s
1+s2
] → (4)
∂u(x;y)
∂y
= −2siny + siny [1 − cosx] −→ (5)
1
su(x; s) − u(x; 0) = 1+s2
[−1 − cosx]
h i
1 1
su(x; s) − u(x; 0) = (1 + cosx) s
− s(1+s2 )
[1 + cosx]
h i
1 1
u(x; s) = (1 + cosx) s
− s(1+s2 )
−→ (6)
This is the required exact solution of equation (7) . Which can be verify through
variables.
Example 3.1.3. Consider the following partial differential equation with Ru(x, y) 6= 0
∂2u ∂u
∂x
+ ∂x
+ u = 6x2 y with initial conditions u(x; 0) = 1 ; u(0; y) = y uy (0; y) = 0
Solution:
∂u(x;y) ∂u(x;y)
In the above example Ru(x; y) = ∂x
+u(x; y) . Use the substitution ∂y
=
14
∂2U ∂u
∂x
+ ∂x
+ u = 6x2 y → (2)
12y
sU (s; y) − U (0; y) + su(s; y) − u(0; y) + Lx [u(x; y)] = s3
12y
U (s; y) = −u(s; y) + s4
− 1s Lx [u(x; y)] → (3)
∂u(x;y)
∂x
= −u(x; y) + 2yx3 − L−1 1
x [ s Lx [u(x; y)]] → (4)
u(x; s) = 1
s
+ 2x3 s13 − 1s Ly [u(x; y) + L−1 1
x [ s Lx [u(x; y)]]] → (5)
u(x; y) = 1 + x3 y 2 − L−1 1 −1 1
y [ s Ly [u(x; y) + Lx [ s Lx [u(x; y)]]]] → (6)
We can not solve the equation (6) because our goal u(x, y) is appeared in both
sides of equation (6) . Thus the equation (1) we can not solve by using LSM because
of Ru(x, y) 6= 0 .
15
Chapter 4
Main Results
∂2u
Example 4.1.1. Consider the partial differential equation ∂x∂y
= e(−y) sinx with
solution:
∂2u
In the above initial value problem Lu(x; y) = ∂x∂y
, h(x; y) = e(−y) sinx and general
∂2u
∂x∂y
= e(−y) sinx → (1)
16
∂U
∂x
= e(−y) sinx → (3)
This is the non-homogeneous partial differential equation of the first order. Taking
1
U (s; y) = e(−y) s(1+S 2 ) → (4)
U (x; y) = e(−y) (1 − cos x)
∂u(x;y)
∂y
= e(−y) (1 − cosx) → (5)
This is the partial differential equation of the first order in the variables x and y .
1
su(x; s) − u(x; 0) = (1 − cosx) (1+S)
1
u(x; s) = (1 − cosx) s(1+S) → (6)
u(x; y) = (1 − cosx) 1 − e(−y)
This is the required exact solution of equation (1) . Which can be verify through
∂2u
Example 4.1.2. Consider the partial differential equation ∂x∂y
= ey cosx with initial
solution:
17
∂2u
In the above initial value problem Lu(x; y) = ∂x∂∂y
, h(x; y) = ey cosx and general
∂2u
∂x∂y
= ey cosx → (1)
∂u
putting ∂y
= U in equation (2) , we get
∂U
∂x
= ey cosx → (3)
This is the non-homogeneous partial differential equation of the first order. Taking
U (s; y) = ey 1s (1+S
s
2) → (4)
U (x; y) = ey sinx
∂u(x;y)
∂y
= ey sinx → (5)
This is the partial differential equation of the first order in the variables x and y .
1
su(x; s) − u(x; 0) = sinx (1−S)
1
u(x; s) = sinx s(1−S) → (6)
18
Taking inverse Laplace transform of equation (6) with respect to y , we get
u(x; y) = sinx(1 − ey )
This is the required exact solution of equation (1) . Which can be verify through
variables.
∂2u
Example 4.1.3. Consider the partial differential equation ∂x∂y
= e(−y) sinx with
solution:
∂2u
In the above initial value problem Lu(x; y) = ∂x∂y
, h(x; y) = e(−y) sinx and general
∂2u
∂x∂y
= e(−y) sinx → (1)
∂u
putting ∂y
= U in equation (2) , we get
∂U
∂x
= e(−y) sinx → (3)
This is the non-homogeneous partial differential equation of the first order. Taking
1
U (s; y) = e(−y) s(1+S 2 ) → (4)
19
Taking inverse Laplace transform of equation (4) with respect to x , we get
U (x; y) = e(−y)) (1 − cos x)
∂u(x;y)
∂y
= e(−y) (1 − cosx) → (5)
This is the partial differential equation of the first order in the variables x and y .
1
su(x; s) − u(x; 0) = (1 − cosx) (1+S)
1
u(x; s) = (1 − cosx) s(1+S) → (6)
u(x; y) = (1 − cosx) 1 − e(−y)
This is the required exact solution of equation (1) . Which can be verify through
variables.
∂2u
Example 4.1.4. Consider the partial differential equation ∂x∂y
= ey sinx with initial
solution:
∂2u
In the above initial value problem Lu(x; y) = ∂x∂y
, h(x; y) = ey sinx and general
∂2u
∂x∂y
= ey sinx → (1)
20
∂ ∂u
∂x ∂y
= ey sinx → (2)
∂u
putting ∂y
= U in equation (2) , we get
∂U
∂x
= ey sinx → (3)
This is the non-homogeneous partial differential equation of the first order. Taking
1
U (s; y) = ey s(1+S 2 ) → (4)
U (x; y) = ey (1 − cosx)
∂u(x;y)
∂y
= ey (1 − cosx) → (5)
This is the partial differential equation of the first order in the variables x and y .
1
su(x; s) − u(x; 0) = (1 − cosx) (1−S)
1
u(x; s) = (1 − cosx) s(1−S) → (6)
u(x; y) = (1 − cosx) 1 − e(y)
This is the required exact solution of equation (1) . Which can be verify through
variables.
21
Example 4.1.5. Consider the following partial differential equation with Ru(x, y) 6= 0
∂2u ∂u
∂x∂y
+ ∂x
+ u = 6xy 2 → (1) with initial conditions u(x; 0) = 1 ; u(0; y) = y ;
uy (0; y) = 0 .
solution:
∂u(x;y) ∂u(x;y)
In the above example Ru(x; y) = ∂x
+u(x; y) . Use the substitution ∂y
=
∂2U ∂u
∂x
+ ∂x
+ u = 6xy 2 → (2)
6y 2
sU (s; y) − U (0; y)+ su(s;y)-u(0;y)+L x [u(x; y)] = s2
6y 2
U (s; y) = −u(s; y) + s3
− 1s Lx [u(x; y)] → (3)
∂u(x;y)
∂x
= −u(x; y) + 3y 2 x2 − L−1 1
x [ s Lx [u(x; y)]] → (4)
u(x; s) = 1
s
+ 6X 2 s14 − Ly [u(x; y) + L−1 1
x [ s Lx [u(x; y)]]] → (5)
We can not solve the equation (6) because our goal u(x, y) is appeared in both
22
sides of equation (6) . Thus the equation (1) we can not solve by using LSM because
of Ru(x, y) 6= 0.
Example 4.1.6. Consider the following partial differential equation with Ru(x, y) 6= 0
∂2u ∂u
∂x∂y
+ ∂x
+ u = 24x2 y 3 → (1) with initial conditions u(x; 0) = 1 ; u(0; y) = y ;
uy (0; y) = 0 .
solution:
∂u(x;y) ∂u(x;y)
In the above example Ru(x; y) = ∂x
+u(x; y) . Use the substitution ∂y
=
∂2U ∂u
∂x
+ ∂x
+ u = 24x2 y 3 → (2)
48y 3
sU (s; y) − U (0; y) + su(s; y) − u(0; y) + Lx [u(x; y)] = s3
48y 3
U (s; y) = −u(s; y) + s4
− 1s Lx [u(x; y)] → (3)
∂u(x;y)
∂x
= −u(x; y) + 8y 3 x3 − L−1 1
x [ s Lx [u(x; y)]] → (4)
u(x; s) = 1
s
+ 48X 3 s15 − Ly [u(x; y) + L−1 1
x [ s Lx [u(x; y)]]] → (5)
23
u(x; y) = 1 + 2x3 y 4 − L−1 1 −1 1
y [ s Ly [u(x; y) + Lx [ s Lx [u(x; y)]]]] → (6)
We can not solve the equation (6) because our goal u(x, y) is appeared in both
sides of equation (6) . Thus the equation (1) we can not solve by using LSM because
of Ru(x, y) 6= 0 .
Example 4.1.7. Consider the following partial differential equation with Ru(x, y) 6= 0
∂2u ∂u
∂x∂y
+ ∂x
+ u = 12xy 2 → (1)
∂2U ∂u
∂x
+ ∂x
+ u = 12xy 2 → (2)
12y 2
sU (s; y) − U (0; y) + su(s; y) − u(0; y) + Lx [u(x; y)] = s2
12y 2
U (s; y) = −u(s; y) + s3
− 1s Lx [u(x; y)] → (3)
∂u(x;y)
∂x
= −u(x; y) + 6y 2 x2 − L−1 1
x [ s Lx [u(x; y)]] → (4)
u(x; s) = 1
s
+ 122 s14 − Ly [u(x; y) + L−1 1
x [ s Lx [u(x; y)]]] → (5)
24
Taking inverse Laplace transform of equation (5) with respect to y , we get
We can not solve the equation (6) because our goal u(x, y) is appeared in both
sides of equation (6) . Thus the equation (1) we can not solve by using LSM because
of Ru(x, y) 6= 0 .
25
Chapter 5
References
[1] Joel L. Schifi, The Laplace Transform: Theory and Applications, springer.
Boundary Value Problems, Seventh Addition, John Wiley and Sons, Inc. (2001)
able).
[6] Standley J.Farlow, Partial Differential Equation’s for Scientists and Engineers.
26
[8] K.Sankara Rao, Introdution to Partial Differential Equation,2 n dEdition.
27